PENGARUH GAYA KEPEMIMPINAN TRASFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA PADANG SATU DENGAN KEPUASAN KERJA SEBAGAI MEDIASI PADA KANTOR PELAYANAN PAJAK PRATAMA PADANG SATU - Lenny Risma Ulina Sinabariba; Rahmy Fahmi (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
Abstract: The study in this study concerning the analysis of the influence of transformational leadership style and organizational culture on the performance of the Padang One Primary Tax Service Office with Job Satisfaction as Mediation ". In this study using descriptive analysis. This analysis is to strengthen the arguments and logic in answering and implementing the allegations that will be described in quantitative analysis, based on those collected from the questionnaire that has been submitted and filled in by 95 employees. Then this data is analyzed statistically using PLS applications. The results of the analysis showed that there was a positive and significant influence between transformational leadership and organizational culture on employee satisfaction, then transformational leadership and organizational culture on employee performance.Keywords: Transformational Leadership, Organizational Culture, Job Satisfaction, Employee Performance